Indústria automobilística como um setor-chave na estrutura produtiva de uma região: o caso do complexo Ford de Camaçari - Gomes, Roberto Alves (2012)
This study aims to analyze the transformations on the Bahia state economy, based on the impacts generated by Northeast’s Ford Industrial Complex and industrial configuration changes in Bahia, as well as identify sectorial linkages and key sectors. We also intend to historically contextualize the automotive industry, through an analysis of the modes of production, the insertion of the Automotive Industry in Brazil and, finally deploying of Ford complex in Bahia in 2001. Through analysis of the automotive supply chain, the study identifies the formation of an industry capable of generating growth in income in the region where it is located. Addressing aspects of the automotive industry's competitiveness on a global scale, this work seeks to bring this discussion from theoretical to empirical field. Finally, the study identifies, through the Input-Output Models (IOM), the economic repercussions occurred in Bahia, the benefits caused by large tax breaks due to the installation of the Ford Complex in Camaçari. Another approach through the IOM will analyze the effects of chaining key sectors and their importance within the economy of Bahia.